(untitled) (Journal of Orofacial Research, 2020)
Oral cancer is a potentially fatal disease which constitutes an important part of tumors occurring in the head and neck region. It not only affects the overall health but also affects the mental health, appearance, employment, social life and family living. It can also cause serious changes in the functioning of the upper aero digestive tract that affects the quality of life in patients. The use of conventional treatment modalities depend on tumor respectability and location as well as feasibility of organ preservation approach. However, their role in oral cancer treatment is non-selective and can cause damage to normal tissue. In particular, chemo radiotherapy is associated with systemic toxicities that often reduce patient compliance and prevent timely completion of therapy. Scientists around the world are now developing a new treatment known as ’green chemoprevention’ in which broccoli and other vegetables are used to prevent the onset of carcinoma. In this review article, the author presents a detailed review about the chemotherapeutic effect of sulforaphane, a dietary component from broccoli sprouts in the prevention of oral cancer.que is a shear-based moment, a force obtained from a twisted spring wire in its effort to un-twist itself which causes rotation. In dentition, it pertains to facio-lingual root movement and control. Also, it refers to the amount of twist applied to an arch wire in bracket engagement or activation. Despite the advent of numerous treatment philosophies, appliance systems and torque prescriptions and considerable research done in the past, torque is still an enigma. The key is to understand not only how we reach where we are but also to learn how to manage the torque properly, focusing on the technical and biomechanical purposes that led to the change of the torque values over time. The present review focuses on application of torque in orthodontics.